The Effectiveness of Audiovisual Media and Leaflets in Enhancing Knowledge, Attitudes, and Practices of Pregnancy Services. - Rahayuningsih, Faizah Betty; Kristinawati, Beti (Universitas Pendidikan Indonesia, 2023)
Introduction : Health education about pregnancy care is important to increase the knowledge of pregnant women so that it will encourage positive attitudes and behavior towards the health of the mother and fetus. Audiovisual media and leaflets are often used to convey health information. Objective : This research aims to determine the differences in the effectiveness of the two media in increasing knowledge, attitudes and practices of pregnancy services for pregnant women at the Tambakromo Community Health Center. Method : This research uses an experimental design with a two group pretest posttest design. The research sample was 76 pregnant women at the Tambakromo Community Health Center who were divided into two groups randomly. The first group was given health education using audiovisual media, and the second group was given leaflet media. Data were analyzed using the Independent Sample T-test and Mann Whitney with p0.05. Result : Respondents' knowledge, attitudes and pregnancy care practices increased after being given health education. Audiovisual media is more effective than leaflet media in increasing knowledge (p-value = 0.004), practice (p-value = 0.007), and attitudes (p-value = 0.010) of pregnant women regarding pregnancy care. Conclusion : Increased knowledge, attitudes and practices show that both media are effective in increasing pregnant women's awareness about the importance of pregnancy checks. However, audiovisual media has proven to be more effective because it is multisensory, making it more interesting and easier to understand. Health education using audiovisual media is more effective than leaflet media in increasing knowledge, attitudes and practices of pregnancy care among pregnant women at the Tambakromo Community Health Center.